2022
DOI: 10.1007/s11160-022-09724-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring temporal patterns in fish feeding ecology: Are ontogenetic dietary shifts stable over time?

Abstract: Disentangling the causes and consequences of ontogenetic niche shifts has been a pivotal challenge in ecology, aiming to enhance the understanding of biological processes that function at the individual, population, and community levels. Studies on ontogenetic dietary shifts have traditionally focused on short time scales, mostly including sampling covering just one or a few consecutive years, thus neglecting possible aspects of temporal variation and ecosystem stability that can only be revealed on long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Similarly, Pirhonen et al [ 24 ] reported that the stomach volume is directly proportional to the weight of fish. A previous study noted that the number of satiations decreases as the bodyweight decreases, suggesting that smaller fish eat relatively higher amounts of food than larger fish [ 25 ].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Pirhonen et al [ 24 ] reported that the stomach volume is directly proportional to the weight of fish. A previous study noted that the number of satiations decreases as the bodyweight decreases, suggesting that smaller fish eat relatively higher amounts of food than larger fish [ 25 ].…”
Section: Discussionmentioning
confidence: 93%
“…Key references included literature from other alpine or sub-arctic lakes in Norway and Scandinavia (e.g., Brittain 1978a , b ; Larsson 1978 ; Lillehammer 1978a , b ), in addition to more general literature for some groups (e.g., Monakov 1972 ; Nilsson 1997 ; Thorp and Covich 2009 ; Beaman and Madge 2010 ). Direct observations of feeding interactions in Takvatn were mainly discerned for the three fish species of charr, brown trout ( Salmo trutta , hereafter trout), and stickleback, from which stomach contents have been analyzed (Amundsen and Klemetsen 1988 ; Klemetsen et al 2002 ; Amundsen et al 2007 ; Prati et al 2020a , b , 2021 ; Sánchez-Hernández et al 2022 ). We included the most important prey items, with a general rule to include prey with > 1% of volume and > 1% of frequency of occurrence in at least one month, from 1999 to 2018 for trout and charr and 2010–2016 for stickleback for different ontogenetic stages (three stages for trout and stickleback and five stages for charr).…”
Section: Methodsmentioning
confidence: 99%
“…Key references included literature from other alpine or sub-arctic lakes in Norway and Scandinavia (e.g., Brittain 1978a, b;Larsson 1978;Lillehammer 1978a, b), in addition to more general literature for some groups (e.g., Monakov 1972;Nilsson 1997;Thorp and Covich 2009;Beaman and Madge 2010). Direct observations of feeding interactions in Takvatn were mainly discerned for the three fish species of charr, brown trout (Salmo trutta, hereafter trout), and stickleback, from which stomach contents have been analyzed (Amundsen and Klemetsen 1988;Klemetsen et al 2002;Amundsen et al 2007;Prati et al 2020aPrati et al , b, 2021Sánchez-Hernández et al Table 2 Summary of the four link categories (consumer-resource) and the 12 link types observed in the pelagic and benthic compartments of the Takvatn food web and the whole-lake food web Link category (consumerresource)…”
Section: Link Assignmentmentioning
confidence: 99%
“…As consumption patterns vary across ontogeny, climate changes can influence trophic relationships across the lifetime of an organism. Arctic char ( Salvelinus alpinus ) and brown trout ( Salmo trutta ), two predatory lake fishes, exhibited dietary shifts with body length facilitating resource partitioning (Sánchez‐Hernández et al, 2022). Shifts in growth rate and maximum size, as a response to climate change, have the potential to uncouple these coexistence relationships, modifying and reducing the stability of food webs (Cheung et al, 2013).…”
Section: Physiological and Phenotypic Pathwaysmentioning
confidence: 99%
“…(b) Mistiming in insect phenology can desynchronize interactions with pollinators (Ohler et al, 2023). (c) Shifts in fish growth rate and maximum sizes may uncouple coexisting resource partitioning, destabilizing food webs (Sánchez‐Hernández et al, 2022). (d) Behavioral responses to environmental change may include seeking refuge or shade, altering times of foraging, or migrating to new habitats; all exposing animals to alternative food resources (Beever et al, 2017).…”
Section: Trophic Pathways For Global Change and Diet Interactionsmentioning
confidence: 99%